Infantile leukocytoclastic vasculitis caused by enterotoxin‐producing methicillin‐sensitive Staphylococcus aureus. Issue 5 (15th July 2021) - Namba, Takahiro; Ebuchi, Yuki; Manabe, Keiko; Shimizu, Junya
Abstract: Staphylococcus aureus infections are known to cause leukocytoclastic vasculitis (LCV). Herein, we describe a case of an 18‐month‐old with LCV caused by enterotoxin‐producing methicillin‐sensitive Staphylococcus aureus (MSSA) emanating from an unrecognized pharyngeal abscess. It is critical to consider the possibility of extracutaneous sources of MSSA infection when investigating an infant with vasculitis. Prompt diagnosis and appropriate treatment are vital in preventing potentially life‐threatening complications.